Forms of rarity of trees in Araucaria forests in Southern of Brazil Formas de raridade de árvores em fragmentos de Floresta Ombrófila Mista no sul do Brasil - Ferreira T.D.S.* (2015)
This study aimed to identify the forms of rarity and their proportions among trees of Araucaria Forest. We developed an abundance matrix of species from sampling units distributed through 11 different fragments in the southern plateau portion of Santa Catarina state. In each sampling unit we counted and identified all the trees that presented diameter at breast height (DBH) . 5 cm. We used a grid of descriptors to find the species belonging to each rarity class, which classified the species into four categories: C= nonscarce euryecious; R1= scarce euryecious; R2= non-scarce stenoecious; R3= scarce stenoecious. Our results showed that from 142 species analyzed, 92 (64.79%) were non-scarce euryecious (C). Five species (3.52%) were classified in the form of rarity R1, 31 (21.83%) in the form of rarity R2 and 14 (9.86%) in the form of rarity R3. The main conditioning factor of the rarity was the habitat preference, i.e., stenoecious species, represented in the forms of rarity R2 and R3. The species classified in the form of rarity R3 are the ones that most need efforts in conservation.